Experimental evidence of icosahedral and decahedral packing in one-dimensional nanostructures - Velázquez Salazar, J. Jesús; Esparza, Rodrigo; Mejía Rosales, Sergio; Estrada Salas, Rubén; Ponce, Arturo; Deepak, Francis Leonard; Castro Guerrero, Carlos Fernando; Yacamán, Miguel José (American Chemical Society, 2011)
Abstract: The packing of spheres is a subject that has drawn the attention of mathematicians and philosophers for centuries and that currently attracts the interest of the scientific community in several fields. At the nanoscale, the packing of atoms affects the chemical and structural properties of the material and, hence, its potential applications. This report describes the experimental formation of 5-fold nanostructures by the packing of interpenetrated icosahedral and decahedral units. These nanowires, formed by the reaction of a mixture of metal salts (Au and Ag) in the presence of oleylamine, are obtained when the chemical composition is specifically Ag/Au = 3:1. The experimental images of the icosahedral nanowires have a high likelihood with simulated electron micrographs of structures formed by two or three Boerdijk Coxeter Bernal helices roped on a single structure, whereas for the decahedral wires, simulations using a model of adjacent decahedra match the experimental structures. To our knowledge, this is the first report of the synthesis of nanowires formed by the packing of structures with 5-fold symmetry. These icosahedral nanowire structures are similar to those of quasicrystals, which can only be formed if at least two atomic species are present and in which icosahedral and decahedral packing has been found for bulk crystals.